Similar tactile distance anisotropy across segments of the arm. (May 2022) - Chang, Kai-Chien; Longo, Matthew R.
A substantial literature has described anisotropy of tactile distance perception across many body parts. In general, the distance between two touches is felt as larger when the touches are oriented with the mediolateral axis of the limbs than when oriented with the proximodistal axis. In this study, we investigated tactile distance perception across the arm, measuring anisotropy on the upper arm, forearm, and hand dorsum. Participants made forced-choice judgments of which of two pairs of tactile distances felt larger and anisotropy was measured using the method of constant stimuli. Clear anisotropy was found on all three regions of the arm. There was no apparent difference in the magnitude of anisotropy across segments of the arm. We further measured the physical curvature of the arm and show that this cannot account of the perceptual anisotropy observed.